Latvijas komercbanku finanšu darbības analīze - Svētiņš, Kristaps (Latvijas Universitāte, 2011)
Bakalaura darba „Latvijas komercbanku finanšu darbības analīze” mērķis ir pētīt banku sistēmu Latvijā, analizēt Latvijas banku sistēmas vēsturisko attīstību un pašreizējo darbību, kā arī veikt Latvijas komercbanku darbības analīzi un izpēti. Bakalaura darbs sastāv no četrām daļām. Autors izvēlējās pirmo nodaļu, lai sniegtu vispārējo informāciju par Latvijas banku sistēmas attīstību no 1991. gada, kādam nolūkam un pēc kādiem principiem tiek veikta komercbanku finanšu analīze. Otrā nodaļa sniedz informāciju par Latvijas komercbanku peļņas un zaudējumu rādītājiem no 2003. līdz 2010. gadam. Trešā nodaļa analizē Latvijas komercbanku sektora pasīvu un aktīvu rādītājus no 2003. līdz 2010. gadam. Ceturtā nodaļa izvērtē un analizē Latvijas komercbanku finanšu rādītājus no 2003. līdz 2010. gadam. Atslēgvārdi: komercbanku analīze, komercbanku attīstība.

The Theses "Analysis of financial performance of commercial banks of Latvia " aims to study the banking system of Latvia, to analyze the Latvian banking system's historical development and currentactivity, as well as Latvian commercial bank performance analysisand research. Thesis consists of four parts. The author has chosen the first chapter in order to present general information of the development of the banking system of Latvia since year 1991, for what purpose and according to what principles the financial analysis of the commercial banks are performed. The second chapter provides information of the indicators of the profit and loss accounts in the sector of commercial banks of Latvia from year 2003 to year 2010. The third chapter analyzes the indicators of assets and liabilities of commercial banks of Latvia from year 2003 to year 2010. The fourth chapter evaluates and analyzes financial indicators of commercial banks of Latvia form year 2003 to year 2010. Keywords: analysis of commercial banks, commercial development.
Latvian commercial bank financial performance analysis
Keywords: Ekonomika